1995
DOI: 10.1109/94.395420
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short HV pulses on bacteria and fungi

Abstract: The survival of three kinds of microorganisms under strongpulse electric field conditions was investigated with a possible application of the electric pulse method for sterilization of consumable liquids. The results of the investigations of survival ratio of Gram-negative (Escherichia coli, Yersinia enterocolitica) and Gram-positive (Staphylococcus aureus, Listeria monocytogenes) bacteria and yeastlike fungi (Candida albicans) are presented. The HV pulses with peak voltage U = 0 to 100 kV and rise time t , = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 12 publications
2
29
0
1
Order By: Relevance
“…Most published data about the influence of microbial characteristics such as the structure and thickness of cell envelopes, cell size and shape on microbial PEF resistance conclude that Gram-positive bacteria are more PEF resistant than Gram-negatives (Aronsson et al, 2001;Hü lsheger et al, 1983;Mazurek et al, 1995;Pothakamury et al, 1995;Vega-Mercado et al,1996), smaller cells more resistant than larger ones and rod-shaped cells less PEF susceptible than sphere-shaped (Heinz et al, 2002;Kehez et al, 1996;Qin et al, 1998).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Most published data about the influence of microbial characteristics such as the structure and thickness of cell envelopes, cell size and shape on microbial PEF resistance conclude that Gram-positive bacteria are more PEF resistant than Gram-negatives (Aronsson et al, 2001;Hü lsheger et al, 1983;Mazurek et al, 1995;Pothakamury et al, 1995;Vega-Mercado et al,1996), smaller cells more resistant than larger ones and rod-shaped cells less PEF susceptible than sphere-shaped (Heinz et al, 2002;Kehez et al, 1996;Qin et al, 1998).…”
Section: Discussionmentioning
confidence: 94%
“…It is assumed that yeast are more sensitive than the vegetative bacteria when intense PEF treatments are applied (Qin et al, 1998;, and Gram-positive bacteria more resistant than the Gram-negatives (Aronsson et al, 2001;Hü lsheger et al, 1983;Mazurek, Lubicki & Staroniewicz, 1995;Pothakamury, Monsalve-González, Barbosa-Cáno-vas & Swanson, 1995;VegaMercado, Martín-Belloso, Chang, Barbosa-Cánovas & Swanson, 1996). Since the mechanism of inactivation by PEF seems to be related to the effects on the cytoplasmic cell membrane, the thicker and more rigid cell envelopes of Gram-positive bacteria have been pointed out to be responsible for their higher PEF resistance.…”
Section: Introductionmentioning
confidence: 97%
“…The electrode was therefore separated from the fluid. This technique has also been used in large-scale PEF equipment [72][73][74][75]. It would be logical to think that such an approach should be copied in future microtechnological structures, for example by applying dedicated coatings [76].…”
Section: Electrode Propertiesmentioning
confidence: 99%
“…The level of microbial inactivation by PEF depends on process parameters including electric field strength, total treatment time, pulse width and pulse waveform, on medium related parameters such as conductivity and composition, on environmental parameters such as temperature, and on microbial parameters such as microbial strain and growth phase (Aronsson & Rö nner, 2001; Barsotti & Cheftel, 1999;Vega-Mercado et al, 1997;Wouters & Smelt, 1997). Numerous laboratory studies have shown that PEF can induce moderate (1 to 3 log cycles) to significant (6 to 9 log cycles) microbial inactivation in various aqueous solutions (Bushnell, Dunn, Clark, & Pearlman, 1993;Ho, Mittal, Cross, & Griffiths, 1995;Marquez, Mittal, & Griffiths, 1997;Mazurek, Lubicki, & Staronieneicz, 1995;Qin et al, 1995;Sato, Kimura, Ikeda, Ogiyama, & Hata, 1994;Zhang et al, 1994;Zhang, Qin, Barbosa-Cánovas, & Swanson, 1995). No apparent changes in physical and chemical properties directly caused by PEF treatment were found in apple juice and cider, cranberry juice, orange juice, raw milk and green pea soup (Dunn, 1996;Evrendilek et al, 2000;Jia, Zhang, & Min, 1999;Jin & Zhang, 1999;Qiu, Sharma, Tuhela, Jia, & Zhang, 1998;Qin et al, 1995;Vega-Mercado, Martín-Belloso, Chang, Barbosa-Cánovas, & Swanson, 1996).…”
Section: Introductionmentioning
confidence: 96%